Evaluasi Kinerja Tarik Taktor Tangan Dengan Bahan Bakar Minyak Kelapa Murni - Desrial .; Yohanes Aris Purwanto; Fandra Wiratama (PERTETA, 2010)
Abstract Past research shown that coconut oil can be used directly in Diesel engine by adding a heating element in the fuel delivery system. This study aims to evaluate the performance of a hand tractor pull using pure coconut oil fuel. The Diesel engine of the tractor was equipped with a fuel heater installed on the mufler. Traction performance parameters tested were wheel slippage, drawbar pull, forward speed and drawbar power on the path of concrete and soil. Besides, the tractor was also tested on plowing using a moldboard plow. The test results on the concrete track showed that the maximum drawbar pull was 1.21 kN generated at a speed of 0.92 m/s, with a maximum drawbar power of 1.21 kW at the wheel slip of 10.87%. While the drawbar pull on the soil track was 1.37 kN at a speed of 0.79 m/s, with a maximum value of 0.71 kW drawbar power when wheels slip 22.25%. The results of tillage test showed that field efficiency was 84.66%, which was not much different from the test result using Diesel fuel. Keywords: fuel heater, Diesel engine, pure coconut oil, drawbar pull performance Diterima: 8 Desember 2009; Disetujui: 16 Maret 2010